Composition and structure of composite building materials - Eshkobilova M.E; Khudoyberdieva F.B (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In today’s industry, fiber-reinforced thermosets and thermoplastics play an important role in production, engineering, usage, and education. This chapter provides an overview of the materials from which a composite can be composed and their most important properties. First, we shall determine what a composite actually is.